1993
DOI: 10.2136/sssaj1993.03615995005700040001x
|View full text |Cite
|
Sign up to set email alerts
|

On Particle‐Size Distributions in Soils

Abstract: Measurements of soil particle‐size distributions have been performed down to 20‐nm radius using, beside classical methods such as sieving and sedimentation, mainly static and dynamic light scattering. The number of particles N per unit volume with a radius larger than r was found to follow a power law N α r−v with the exponent v = 2.8 ± 0.1. This exponent was observed in all soils investigated and can be interpreted as the fractal dimension of an underlying structure. The power law usually held over two to fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
58
0
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(66 citation statements)
references
References 0 publications
5
58
0
3
Order By: Relevance
“…These results indicated that LDM underestimated clay content relative to SPM by an average of 45.1% but overestimated silt content by an average of 18.3% in the soils of the Loess Plateau, consistent with other findings for diverse soil textures (Loizeau et al, 1994;Konert and Vandenberghe, 1997;Eshel et al, 2004;Shein et al, 2006;Yang et al, 2009;Wang et al, 2013a). Beuselinck et al (1998), however, reported that LDM underestimated the clay fraction of silty soils but generally overestimated the clay fraction of milled quartz samples, and Wu et al (1993) and Muggler et al (1997) reported agreement between the two methods.…”
Section: Comparison Of Particle-size Distributions Between Laser-diffsupporting
confidence: 88%
See 1 more Smart Citation
“…These results indicated that LDM underestimated clay content relative to SPM by an average of 45.1% but overestimated silt content by an average of 18.3% in the soils of the Loess Plateau, consistent with other findings for diverse soil textures (Loizeau et al, 1994;Konert and Vandenberghe, 1997;Eshel et al, 2004;Shein et al, 2006;Yang et al, 2009;Wang et al, 2013a). Beuselinck et al (1998), however, reported that LDM underestimated the clay fraction of silty soils but generally overestimated the clay fraction of milled quartz samples, and Wu et al (1993) and Muggler et al (1997) reported agreement between the two methods.…”
Section: Comparison Of Particle-size Distributions Between Laser-diffsupporting
confidence: 88%
“…For example, LDM underestimated clay fractions and overestimated silt fractions compared with SPM (Konert and Vandenberghe, 1997;Beuselinck et al, 1998;Eshel et al, 2004;Yang et al, 2009). A few study, however, reported good agreement between the two methods (Wu et al, 1993;Muggler et al, 1997;Cheetham et al, 2008). These differences in PSDs between the two methods were due to differences in methodology, mineralogy, refraction index values of the samples, and particle morphology (Zobeck, 2004).…”
mentioning
confidence: 99%
“…By the same token, Prosperini and Perugini (2008) partitioned the whole PSD of soil samples into two fractal scaling domains and obtained the fractal dimensions ranging from 0 to 3. Millán et al (2003) compared the fitness of piecewise fractal model with nonlinear and log-linear regressions by using the experimental data of the PSD for a clay soil and a loam soil (Wu et al 1993, Bird et al 2000. The linear regression to log-transformed data showed some lack of fit, as reflected by the low coefficient of determination (0.75), whereas the piecewise law with respect to high correlation (0.98) is regarded to be better.…”
Section: Piecewise Fractal Modelmentioning
confidence: 99%
“…Primary minerals originate from weathering of a parent material, and generally present in the sandand silt-sized fractions, while secondary minerals such as clay minerals are the result of formation of new minerals (Wu et al 1993;Posadas et al 2001). Particle-size distributions of soils are often used to estimate other soil properties such as soil moisture characteristics and hydraulic conductivity (Bittelli et al 1999;Khodaverdiloo et al 2011), thus accurate estimation of soil properties strongly depends on the accuracy of particle size determination.…”
Section: Introductionmentioning
confidence: 99%